2017
DOI: 10.1055/s-0037-1604286
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics of a Fatal Ruptured Anterior Communicating Artery Aneurysm

Abstract: Computational fluid dynamics (CFD) has been studied as a tool for the stratification of aneurysm rupture risk. We performed CFD analysis in a patient operated on for a ruptured anterior communicating artery aneurysm. The point of rupture was identified during surgery. The aneurysm and blood vessels were segmented from computed tomography angiography to prepare a model for simulations. We found that the streamlines showed a concentrated inflow jet directed straight at the rupture point, and high wall shear stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Several previous studies have analyzed the local hemodynamics at rupture sites, either identified during open surgery (or intraoperative videos) 13,17,[21][22][23][24] or by analyzing blood extravasation in 3D images. [14][15][16][18][19][20]25 Although these studies did not analyze the location of the rupture site with respect to different aneurysm regions, it was possible to determine the rupture site location with respect to the different aneurysm regions considered here of some aneurysms that were visible in the figures presented in these papers.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have analyzed the local hemodynamics at rupture sites, either identified during open surgery (or intraoperative videos) 13,17,[21][22][23][24] or by analyzing blood extravasation in 3D images. [14][15][16][18][19][20]25 Although these studies did not analyze the location of the rupture site with respect to different aneurysm regions, it was possible to determine the rupture site location with respect to the different aneurysm regions considered here of some aneurysms that were visible in the figures presented in these papers.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The hemodynamics at the rupture site have been analyzed in very limited cases, with roughly 58 rupture sites from 13 published studies. [13][14][15][16][17][18][19][20][21][22][23][24][25] However, the results are confusing, particularly the role of WSS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outlet condition that prescribes zero stress vectors [41] is considered to be the same as Eq. (8).…”
Section: Conditions On Velocity Gradientmentioning
confidence: 99%
“…It might be inappropriate to impose the traction-free condition onto cases when daughter arteries are extended by adding straight pipes because flows are being developed in the straight pipes. In fact, researchers using the tractionfree condition simply truncated distal arteries, not applying the outlet extension to their 3-D models [28,[41][42][43][44]. Xu et al [29], instead, adopted zero velocity-gradient in the normal direction for models with extended outlets.…”
Section: Conditions On Velocity Gradientmentioning
confidence: 99%